2016
DOI: 10.1088/1748-6041/11/1/015005
|View full text |Cite
|
Sign up to set email alerts
|

Study of the mechanical stability and bioactivity of Bioglass ® based glass-ceramic scaffolds produced via powder metallurgy-inspired technology

Abstract: Large bone defects are challenging to heal, and often require an osteoconductive and stable support to help the repair of damaged tissue. Bioglass-based scaffolds are particularly promising for this purpose due to their ability to stimulate bone regeneration. However, processing technologies adopted so far do not allow for the synthesis of scaffolds with suitable mechanical properties. Also, conventional sintering processes result in glass de-vitrification, which generates concerns about bioactivity. In this w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 37 publications
1
16
0
Order By: Relevance
“…Before examining the results obtained in the present work relatively to the behavior displayed by these three groups of samples during in vitro tests, some preliminary considerations are worth to be made. In particular, it should be mentioned that the physiological media used in various studies reported in the literature were periodically refreshed . Such choice was aimed to maintain the ions concentration more stable during the test.…”
Section: Discussionmentioning
confidence: 99%
“…Before examining the results obtained in the present work relatively to the behavior displayed by these three groups of samples during in vitro tests, some preliminary considerations are worth to be made. In particular, it should be mentioned that the physiological media used in various studies reported in the literature were periodically refreshed . Such choice was aimed to maintain the ions concentration more stable during the test.…”
Section: Discussionmentioning
confidence: 99%
“…It is a major challenge using autologous decellularized bone, which promotes donor site morbidity, while there is an increased risk of disease transmission and immune response using allogenic decellularized bone. Several promising synthetic options also exist, such as glass–ceramic, hydroxyapatite, fibronectin, alginate, and biphasic calcium phosphate, which reduce the risk of an immunological response but may lack material properties and factors native to human bone, which would reduce their efficacy as scaffolds. There is continued effort to design an implantable natural or synthetic scaffold with stem cells or bioactive factors that modulates a subsequent immunological response that consists of native‐like biological materials to regenerate bony defects …”
Section: Tissue Engineeringmentioning
confidence: 99%
“…[4][5][6] The 45S5 BG composition (in mol% 46.1% SiO 2 , 24.4% Na 2 O, 26.9% CaO and 2.6% P 2 O 5 ) 4 has been used for several clinical purposes, eg dental and orthopedic applications, and as monolith or in particulates form in non-load-bearing sites. The main difficulty is to fabricate highly porous scaffolds with mechanical strength comparable to that of natural cancellous bone (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12). The main difficulty is to fabricate highly porous scaffolds with mechanical strength comparable to that of natural cancellous bone (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%
“…The main difficulty is to fabricate highly porous scaffolds with mechanical strength comparable to that of natural cancellous bone (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12). [9][10][11] In this way, it was possible to obtain superior mechanical properties without affecting the bioactivity of the starting material and without compromising the possible cell ingrowth and neovascularization of the three-dimensional structure. [9][10][11] In this way, it was possible to obtain superior mechanical properties without affecting the bioactivity of the starting material and without compromising the possible cell ingrowth and neovascularization of the three-dimensional structure.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation